The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.14444/3033
|View full text |Cite
|
Sign up to set email alerts
|

Bone substitutes and expanders in Spine Surgery: A review of their fusion efficacies

Abstract: Study Design A narrative review of literature. ObjectiveThis manuscript intends to provide a review of clinically relevant bone substitutes and bone expanders for spinal surgery in terms of efficacy and associated clinical outcomes, as reported in contemporary spine literature. Summary of Background DataEver since the introduction of allograft as a substitute for autologous bone in spinal surgery, a sea of literature has surfaced, evaluating both established and newly emerging fusion alternatives. An understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 199 publications
0
63
0
Order By: Relevance
“…Future testing of combinations such as these may reveal synergies not apparent on the single material experiment presented here. However, the results of this study help to address the paucity of clinical data 82 and preclinical data to support decisions on selection of individual grafting materials to optimize bone healing in spinal fusion.…”
Section: Resultsmentioning
confidence: 99%
“…Future testing of combinations such as these may reveal synergies not apparent on the single material experiment presented here. However, the results of this study help to address the paucity of clinical data 82 and preclinical data to support decisions on selection of individual grafting materials to optimize bone healing in spinal fusion.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison to previous studies, which show either an inferiority of calcium phosphates compared to autograft or equivalence evidenced through weaker endpoints, we demonstrate equivalent performance of AG, BCP granules and BCP putty by an array of strong assessment methods. In clinical literature, we can find conflicting evidence about the efficacy of calcium phosphate materials as bone graft materials for spine fusion . Physicochemical properties of biomaterials are rarely discussed in clinical literature and it is often overlooked that these properties strongly influence the performance of calcium phosphate bone graft materials.…”
Section: Discussionmentioning
confidence: 99%
“…Symbols: * P < 0.01; ** P < 0.001; # all significantly different from 6 weeks, P < 0.001; † all significantly different from 12 weeks and 6 weeks, P < 0.001; ‡ significantly different from BCP granules , 6 weeks, P < 0.01; • significantly different from BCP granules , 26 weeks, P < 0.05 evidence about the efficacy of calcium phosphate materials as bone graft materials for spine fusion. 36,37 Physicochemical properties of biomaterials are rarely discussed in clinical literature and it is often overlooked that these properties strongly influence the performance of calcium phosphate bone graft materials. Indeed, during preclinical in vivo studies, grafts with optimized physicochemical properties have presented better outcomes than those with suboptimal properties.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have reported the safety and efficacy of DBM as a bone graft extender in lumbar spine fusion (5)(6)(7)(8). One study in 120 patients undergoing 1-2 level instrumented posterolateral fusion (PLF) used a DBM gel (Grafton R ) mixed with local autograft bone implanted on one side, compared to iliac crest autograft implanted on the contralateral side in the same patient (9).…”
Section: Introductionmentioning
confidence: 99%